The challenges and solutions in the management faraid cases: a study in Kota Bharu Syariah Court - Hasmuni, Nur Hidayah (2025)
In Malaysia, the management of inheritance for Muslims is handled by three key institutions: the High Court, the Small Estate Distribution Unit under the Department of Director General of Lands and Mines (JKPTG), and Amanah Raya Berhad (ARB). Meanwhile, the Syariah Court primarily issues faraid certificates and is referred to in cases involving collateral issues in inheritance management and administration, such as marriage validity, heir verification, and inheritance rights. The Syariah Court plays a crucial role in upholding justice by ensuring rightful heirs receive their due rights. This study aims to examine the challenges faced in managing faraid cases at the Syariah Court in Kota Bharu. To achieve this objective, the researcher conducted an intensive study using qualitative methods. Structured interviews were conducted with five respondents working at the Syariah Court in Kota Bharu, all of whom were involved in managing faraid cases. The findings revealed several issues faced by the Syariah Court in handling faraid cases, such as difficulties in locating distant heirs, dishonest applicants, lack of cooperation from heirs, incomplete documents, and constraints in calculation systems, which are major factors delaying the inheritance distribution process. Furthermore, the study highlighted dissatisfaction among staff regarding the system used to manage faraid cases, particularly for registration and calculation purposes. Respondents expressed a preference for the e-Syariah version 2 system over the newer e-Syariah version 3 launched by the Department of Syariah Judiciary Malaysia (JKSM).